Field assessment of corn yield losses and compensatory yield for infested plants by Lepidopteran stem borers in different sowing dates at El-Behiera governorate, Egypt. - Al-Eryan M. A. S; Abu- Shall Amany M. H.; Ibrahiem H. K.; Hussein Hanaa S. (JOURNAL OF ADVANCES IN BIOLOGY, 2020)
Whenever the determination of yield loss and economic injury levels are essential tools for initiating integrated pest management (IPM) programs in the maize field, the assessment of compensatory yield is very important for determinate the accurate losses in the field and the recovery power for the maize verity. The present study aimed to estimate the yield losses of three maize varieties due to Sesamia critica and Ostrinia nubilalis, infestation; regression between maize yield losses and percent of infestation and determine the compensatory yield arising in intact plants as a result of absence or dead (caused by infestation) of adjacent plants under field conditions in El-Behiera governorate. The present results showed that yield losses resulting from S. cretica infestation in early sowed maize ranged from 5.29 – 32.17%. In case of maize that sowed in recommended date “June”, yield losses due to S. cretica was slightly decreased, and it accompanied with O. nubilalis infestation in two fields, which increased the total yield losses. A simple linear regression turned out between the percentage of infestation of S. cretica or O. nubilalis and percentage of yield losses, with R2 values 0.84 and 0.45, respectively. The yellow corn was more tolerant to stem borers infestation than white corn with percentages of increase rate in compensatory yield 27.07 %. Whenever the determination of yield loss and economic injury levels are essential tools for initiating integrated pest management (IPM) programs in the maize field, the assessment of compensatory yield is very important for determinate the accurate losses in the field and the recovery power for the maize verity. The present study aimed to estimate the yield losses of three maize varieties due to Sesamia critica and Ostrinia nubilalis, infestation; regression between maize yield losses and percent of infestation and determine the compensatory yield arising in intact plants as a result of absence or dead (caused by infestation) of adjacent plants under field conditions in El-Behiera governorate. The present results showed that yield losses resulting from S. cretica infestation in early sowed maize ranged from 5.29 – 32.17%. In case of maize that sowed in recommended date “June”, yield losses due to S. cretica was slightly decreased, and it accompanied with O. nubilalis infestation in two fields, which increased the total yield losses. A simple linear regression turned out between the percentage of infestation of S. cretica or O. nubilalis and percentage of yield losses, with R2 values 0.84 and 0.45, respectively. The yellow corn was more tolerant to stem borers infestation than white corn with percentages of increase rate in compensatory yield 27.07 %.